Prevalence of selected birth defects by maternal nativity status, United States, 1999–2007. Issue 11 (28th March 2019) - Kirby, Russell S.; Mai, Cara T.; Wingate, Martha S.; Janevic, Teresa; Copeland, Glenn E.; Flood, Timothy J.; Isenburg, Jennifer; Canfield, Mark A.; ,
Abstract : Objectives: We investigated differences in prevalence of major birth defects by maternal nativity within racial/ethnic groups for 27 major birth defects. Methods: Data from 11 population‐based birth defects surveillance systems in the United States including almost 13 million live births (approximately a third of U.S. births) during 1999–2007 were pooled. We calculated prevalence estimates for each birth defect for five racial/ethnic groups. Using Poisson regression, crude and adjusted prevalence ratios (aPRs) were also calculated using births to US‐born mothers as the referent group in each racial/ethnic group. Results: Approximately 20% of case mothers and 26% of all mothers were foreign‐born. Elevated aPRs for infants with foreign‐born mothers were found for spina bifida and trisomy 13, 18, and 21, while lower prevalence patterns were found for pyloric stenosis, gastroschisis, and hypospadias. Conclusions: This study demonstrates that birth defects prevalence varies by nativity within race/ethnic groups, with elevated prevalence ratios for some specific conditions and lower prevalence for others. More detailed analyses focusing on a broader range of maternal behaviors and characteristics are required to fully understand the implications of our findings.